1991
DOI: 10.1113/jphysiol.1991.sp018784
|View full text |Cite
|
Sign up to set email alerts
|

Rapid resetting of human baroreflex working range: insights from sympathetic recordings during acute hypoglycaemia.

Abstract: SUMMARY1. Human muscle nerve sympathetic activity (MSA), which is governed by baroreflexes and involved in blood pressure homeostasis, is increased during acute insulin-induced hypoglyeaemia.2. To elucidate the detailed relationship between MSA and blood pressure during hypoglyeaemia, 0-15 i.u. (kg body weight)-' regular human insulin was given intravenously to eight fasting, healthy volunteers. Microneurographic recording of MSA in the peroneal nerve was made with simultaneous monitoring of arterial blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For example: 1) transient blockade of peripheral chemoreceptors with hyperoxia temporarily increases baroreflex sensitivity in heart failure patients 2 , 2) unilateral carotid body resection in a human heart failure patient resulted in an improvement in baroreflex sensitivity 24 , 3) activation of the peripheral chemoreceptors with hypoxia decreases baroreflex sensitivity 4 . In addition, previous studies have shown antecedent hypoglycemia to reduce baroreflex sensitivity 25 and reset the baroreflex working range 26 . Our lab has recently shown the baroreflex working range is reset to higher heart rates such that systolic blood pressure is relatively maintained during hypoglycemia 5 .…”
Section: Discussionmentioning
confidence: 97%
“…For example: 1) transient blockade of peripheral chemoreceptors with hyperoxia temporarily increases baroreflex sensitivity in heart failure patients 2 , 2) unilateral carotid body resection in a human heart failure patient resulted in an improvement in baroreflex sensitivity 24 , 3) activation of the peripheral chemoreceptors with hypoxia decreases baroreflex sensitivity 4 . In addition, previous studies have shown antecedent hypoglycemia to reduce baroreflex sensitivity 25 and reset the baroreflex working range 26 . Our lab has recently shown the baroreflex working range is reset to higher heart rates such that systolic blood pressure is relatively maintained during hypoglycemia 5 .…”
Section: Discussionmentioning
confidence: 97%
“…Systolic blood pressure was lower in the E2 group versus the male subjects, and mean arterial pressure responses were lower in both groups of women compared with the male subjects. The baroreflex is reset with hypoglycemia (42), and although unknown, it is possible that sex further impacts the normal baroreflex response to hypoglycemia. Alternatively, men have been found to have greater responsiveness to epinephrineinduced changes in blood pressure (41) and norepinephrine-induced vasoconstriction (43), suggesting that men may simply be more sensitive to catecholamine-induced changes in blood pressure.…”
Section: Figmentioning
confidence: 99%
“…there is a rise in pulse pressure; Hilsted et al 1984). With a detailed study of the beat‐to‐beat relationship between MSNA and diastolic blood pressure, we could demonstrate an acute resetting of the arterial (high pressure) baroreflex working range during hypoglycaemia and subsequent glucose counter‐regulation (Fagius & Berne 1991). The blood pressure levels at which bursts of MSNA occurred were altered but the baroreflex sensitivity remained unchanged.…”
Section: Muscle Sympathetic Nerve Activitymentioning
confidence: 99%